Mechanical and Durability Properties of Sustainable Self-compacting Concrete with Waste Glass Powder and Silica Fume - Jalalinejad, Mahdi; Hemmati, Ali; Mortezaei, Alireza (Periodica Polytechnica Civil Engineering, 2023)
Environmental protection approach has caused to ignore the conditions and the possibility of using solid waste as a substitute for concrete. In this research, the effect of glass powder in percentages of 0-30 (in steps of 7.5%) and micro-silica (10% as a constant) as a substitute for cement is investigated on efficiency, compressive strength, tensile strength, and bending strength. surface water absorption, capillary water absorption, and freeze/thaw cycle are paid. The results showed that the use of glass powder leads to increases the fluidity and properties of fresh concrete. The mechanical parameters decrease slightly when 30% of cement is replaced with glass powder.